Effectiveness of low-dose topical atropine in preventing the progression of myopia – A prospective interventional cohort study in pediatric patients - Tara Susan Mohan; Liji Menon; Mary Shimy; Binu Balan; Latha Panicker (The Pan-American Journal of Ophthalmology)
Background: Myopia is a very common pathological condition in the pediatric age group which can lead to devastating complications if not treated early. Recent studies support the use of atropine drops of various concentrations to prevent the progression of myopia in children. Not many studies have been published from India in this regard. Aims and Objectives: We attempt to assess the effectiveness of low-dose atropine (0.01%) in preventing myopia progression in children. Materials and Methods: 80 eyes of 40 myopic children who attended our Institute were studied after dividing them into control and test groups and followed up for a period of 1 year. Results: Significant reductions in change in axial length and refractive error were noted at the end of 1 year. There is no significant pupillary dilatation with the use of 0.01% atropine and side effects like photophobia were not reported. Conclusion: We concluded that atropine sulfate 0.01% is safe and effective in slowing down the progression of myopia.